Missionary teachers as agents of colonialism: A study of their activities in Uganda, 1877-1925 - Tiberondwa, Ado K. (Kenneth Kaunda Foundation, 1989)
The author reveals the collaboration between European imperial trading companies and colonialists on the one hand, and the missionaries on the other, in entrenching political, economic and cultural imperialism in Uganda, using education and christianity as tools. His thesis is founded on evidence drawn from letters, diaries and annual reports of missionaries as well as colonial administrators